2023
DOI: 10.1097/tp.0000000000004787
|View full text |Cite
|
Sign up to set email alerts
|

Thermoablative Treatment of De Novo Tumor in Kidney Allograft

Sylvain Bodard,
Idris Boudhabhay,
Charles Dariane
et al.

Abstract: Background. The overall cancer risk increases in transplant patients, including in kidney allografts. This study aimed to analyze the outcome of patients with kidney allograft malignant tumors who underwent percutaneous thermal ablation. Methods. We included 26 renal allograft tumors, including 7 clear-cell renal cell carcinoma (RCCs), 16 papillary RCCs, 1 clear-cell papillary RCC, and 2 tubulocystic RCCs, treated in 19 ablation sessions. Outcomes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Regarding to the therapeutic effects, TA could provide more favorable perioperative outcomes and possible long‐term RF preservation compared with PN, 83,158 and previous research also revealed similar short‐ and medium‐term cancer‐specific results 159 . It should be noted that this seems true even for transplant patients carrying a tumor on their kidney graft despite the few studies available 160 . However, a contemporary meta‐analysis demonstrated that TA conferred lower local recurrence‐free survival with one treatment, while reaching therapeutic equivalences with PN only after multiple treatments 161,162 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Regarding to the therapeutic effects, TA could provide more favorable perioperative outcomes and possible long‐term RF preservation compared with PN, 83,158 and previous research also revealed similar short‐ and medium‐term cancer‐specific results 159 . It should be noted that this seems true even for transplant patients carrying a tumor on their kidney graft despite the few studies available 160 . However, a contemporary meta‐analysis demonstrated that TA conferred lower local recurrence‐free survival with one treatment, while reaching therapeutic equivalences with PN only after multiple treatments 161,162 .…”
Section: Discussionmentioning
confidence: 59%
“… 159 It should be noted that this seems true even for transplant patients carrying a tumor on their kidney graft despite the few studies available. 160 However, a contemporary meta‐analysis demonstrated that TA conferred lower local recurrence‐free survival with one treatment, while reaching therapeutic equivalences with PN only after multiple treatments. 161 , 162 Moreover, the therapeutic effect for cT1a patients was compared between different TA methods (heat‐based TA and cryoablation).…”
Section: Discussionmentioning
confidence: 99%